The Evolution of Asthma Management: A Comprehensive Analysis of GINA 2024 Guidelines, Endotype-Driven Diagnosis, and Targeted Biologic Intervention - Kuldeep Kate; Gopal Lohiya; Kranti Satpute; Prakash Honrao; Aniket Salunke; Yogesh Chavan (Recent Trends in Infectious Diseases, 2026)
Asthma remains a substantial global public health challenge, characterized by heterogeneous airway inflammation leading to variable airflow obstruction. Recent advances in personalized medicine and guideline revisions, notably the Global Initiative for Asthma (GINA) 2024 update, mandate a profound paradigm shift from reliance on short-acting beta2-agonists (SABA) to antiinflammatory reliever (AIR) strategies utilizing inhaled corticosteroid (ICS)-formoterol. This report provides an exhaustive analysis of current asthma epidemiology, molecular pathogenesis distinguishing between Type 2 (T2)-high and T2-low endotypes—and contemporary diagnostic standards. A detailed clinical case study of a 9-year-old boy with severe eosinophilic asthma is presented to demonstrate the transformative efficacy of targeted biological therapy (Mepolizumab) in achieving clinical and functional reversal following a severe infectious exacerbation. The synthesis underscores the necessity of meticulous phenotyping, adherence assessment, and comorbidity management as prerequisites for achieving disease control and optimizing resource allocation in advanced severe asthma care.
Keywords: Airway Remodelling; Anti-inflammatory Reliever (AIR); Asthma; Biologics; Eosinophilic Asthma; GINA 2024; Mepolizumab; Paediatric Asthma; Sars-CoV-2